2011
DOI: 10.1590/s1984-70332011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Sources of resistance to Curtobacterium flaccumfaciens pv. flaccumfaciens in common bean accessions

Abstract: The purpose of this study was to identify common bean genotypes resistant to bacterial wilt to be used as resistance sources in breeding programs targeting resistant cultivars. A total of 67 accessions, five cultivars and one control were evaluated, which were artificially inoculated with the Curtobacterium flaccumfaciens pv. flaccumfaciens isolate Cff 2634. The results prove the existence of alleles that confer tolerance to bacterial wilt in the cultivars IAC Carioca Aruã, IAC Carioca Pyatã and IAC Carioca Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The resistance observed in the cultivars IAC Alvorada and IAC Diplomata was probably inherited from IAC Carioca Pyatã, which is one of their parents (Carbonell et al 2008), known for its good levels of Cff-resistance (Maringoni 2002, Camara et al 2009, Valentini et al 2011b). The cul- tivars IPR Corujinha, IPR Tangará, and IAPAR Siriri were described as moderately Cff-resistant (Comissão 2012), in partial agreement with our results, since the cultivars IPR Corujinha and IPR Tangará were considered resistant in this study, while IAPAR Siriri was considered moderately resistant ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistance observed in the cultivars IAC Alvorada and IAC Diplomata was probably inherited from IAC Carioca Pyatã, which is one of their parents (Carbonell et al 2008), known for its good levels of Cff-resistance (Maringoni 2002, Camara et al 2009, Valentini et al 2011b). The cul- tivars IPR Corujinha, IPR Tangará, and IAPAR Siriri were described as moderately Cff-resistant (Comissão 2012), in partial agreement with our results, since the cultivars IPR Corujinha and IPR Tangará were considered resistant in this study, while IAPAR Siriri was considered moderately resistant ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Rava et al (2004) found high levels of Cff-resistance in the common bean accessions Mulatinho, FeijãoBranco, Desconhecido, Amarelinho, Enxofre/Amarelo, Coquinho Enxofre, Jalinho, Amarelo Arroxeado, Rapezão, Feijão Mourinho, Feijão Baetão, and Vermelho 1 Epamig, among a total of 333 accessions of Embrapa Rice and Beans. According to Theodoro and Maringoni (2006), the cultivars Mouro Pirituba and Vagem Amarela have satisfactory levels of Cff-resistance, and Valentini et al (2011b) identified a certain level of resistance in the common bean accession BAF 122, and in the cultivars IAC Carioca Akytã, IAC In these studies, the plants were inoculated by puncturing the stem, which, according to Krause et al (2009), is more satisfactory than inoculation by injuries at the seed hilum or cutting seedling roots to evaluate the Cff-resistance reaction of common bean plants.…”
Section: Introductionmentioning
confidence: 99%
“…flaccumfaciens, that so far have been identified outside the EU. Among them, only some are considered suitable for commercial production (Maringoni, 2002;Souza et al, 2006;Valentini et al, 2011;Urrea and Harveson, 2014).…”
Section: Host Rangementioning
confidence: 99%